2021
DOI: 10.1215/00703370-8977484
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Strategies for Investigating the Mechanisms Linking Climate and Individual-Level Child Health Outcomes: An Analysis of Birth Weight in Mali

Abstract: The goal of this article is to consider data solutions to investigate the differential pathways that connect climate/weather variability to child health outcomes. We apply several measures capturing different aspects of climate/weather variability to different time periods of in utero exposure. The measures are designed to capture the complexities of climate-related risks and isolate their impacts based on the timing and duration of exposure. Specifically, we focus on infant birth weight in Mali and consider l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…The results also show that greater amounts of precipitation and higher temperatures are associated with reduced WHZ scores. While elevated temperatures are commonly associated with worse health outcomes (Thiede & Strube, 2020), rainfall is often positively associated with health outcomes, although not consistently (Grace et al, 2021;Randell et al, 2020;…”
Section: Nigeriamentioning
confidence: 99%
“…The results also show that greater amounts of precipitation and higher temperatures are associated with reduced WHZ scores. While elevated temperatures are commonly associated with worse health outcomes (Thiede & Strube, 2020), rainfall is often positively associated with health outcomes, although not consistently (Grace et al, 2021;Randell et al, 2020;…”
Section: Nigeriamentioning
confidence: 99%
“…Previous studies have examined the costs of precipitation extremes for child health at both the global and national scale (Arnell et Grace et al 2021). Many studies have also not fully accounted for key biological periods of exposure to climate shocks, for potential vulnerability across different socio-demographic groups, or for spatial correlates of climate that might confound the results (Randell et Funk et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we know that children's vulnerability to climate shocks does not remain constant throughout their early years (Shrimpton et al 2001, Victora et al 2009, Headey et al 2015; evidence shows that exposure to extreme weather during the first 1,000 days after conception can have adverse developmental effects that last into adulthood and are linked to educational, financial, and physical deficits 2019) explored the nutritional effects of both precipitation extremes in 53 countries and found that while children's heights steadily declined as conditions got drier, they declined even more steeply during wet periods-but only when the rain was very extreme. Others have found mixed effects of climate shocks that vary significantly according to spatial location, demographic characteristics, and timing of exposure (Shively et al 2015;Grace et al 2021;Nicholas et al 2021). In linking climate with birth outcomes in Mali, Grace et al (2021) found that precise metrics and consideration of exposure timing-down to the trimester level, for prenatal exposure-are especially important when analyzing the impacts of precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations